Aquatic macroinvertebrates in Uruguayan rice agroecosystem - Bao, Leticia (Biodivers Data J, 2021)
This work is a first approach to the knowledge of insects and other aquatic macroinvertebrates of rice agroecosystems from eastern Uruguay. The composition of the groups collected may represent an approximation to the knowledge of the quality of water sources associated with Uruguayan rice production. Sampling of aquatic macroinvertebrates was carried out during the grain-filling stage in crops without insecticide use, in three localities of Treinta y Tres Department. In each crop, macroinvertebrates were collected with a Surber-type network at the inlet and outlet of water to and from the paddy field and a neighbouring control area. Differences in morphospecies composition were found according to the location and source of water. Insecta was the most represented class in macroinvertebrate samplings (41.5%). Diptera (59.9%), Hemiptera (16.3%) and Ephemeroptera (14.0%) were the most abundant orders within insects. The Richness and Shannon Diversity Indices were higher than those recorded for similar studies in Costa Rica, Italy and Australia.